Bio-Sorbent Optimisation Through Chemical Activation in The Processing of Waste Water in The Oil and Gas Sector - Rika Lala Saputri; Muhammad Khairul Afdhol; Tomi Erfando; Fiki Hidayat; Razif Muhammed Nordin (Scientific Contributions Oil and Gas, 2025)
The oil and gas industry is renowned for producing water that posed significant threat to the environment, making its management a significant concern. Therefore, the purpose of this research is to evaluate the efficiency of different bio-sorbents in purifying treated wastewater. The bio-sorbents used were derived from cashew shells (KMR), jenitri fruit (JNT), and walnuts (WN). This led to the introduction of a new method, which combined different chemical activations with various bio-sorbents, alongside characterization and filtration performance evaluations. This resulted in high-performance bio-sorbents for produced water treatment. Additionally, the methods adopted include adsorbent preparation, characterization (bulk density, FTIR, SEM), and filtration testing for turbidity and TDS parameters. The results showed that chemical activation significantly enhanced adsorbent performance, with candlenut shell + zinc chloride (KMR+ZC) and jenitri + potassium hydroxide (JNT+K) exhibiting the best adsorption capacity. Bulk density analysis showed a decrease in value after chemical activation, showing increased porosity. Meanwhile, FTIR characterization confirmed changes in functional groups after activation, with SEM showing structure modifications that improved adsorption surface area. Filtration tests showed that the modified adsorbents had better capacity in reducing turbidity and TDS in treated water.